THE IMPACT OF EROSION-SEDIMENTATIONS TO SILTATION OF KENDARI BAY AND IMPLICATIONS IN TOURISM DEVELOPMENT OF SOUTHEAST SULAWESI, INDONESIA - Sukiyah, Emi; Jassin, A.M.I.; Fachrudin, Kurnia Arfiansyah (Journal of Geological Sciences and Applied Geology, 2021)
Kendari Bay is a strategic area, especially for Southeast Sulawesi Province. There lies Kendari city as the provincial capital. The government is intensively developing tourism to increase local revenue. Tourism potential that can be developed includes marine tourism, mangrove tracking, and Tahura forest as the lungs of Kendari City. Sedimentation in the bay is a major problem of silting. Sediment comes from the erosion in Kendari drainage basin. The rivers that carry material of erosion products, mostly boils down in Kendari Bay. This condition can threaten the development of tourism in the bay area. Monitoring of erosion and sedimentation should be done on an on-going basis.  USLE formula be used calculate erosion rate. Several factors combined for reasons of easiness in the process of data acquisition. The data source obtained by various methods, one of them is satellite imagery processing. The study uses images of Landsat 8 OLI 2013 and SRTM 30 m. The whole data are processed using GIS software. The results showed that erosion rate in the area categorized moderate until very high level. The tree planting of upstream area and sediment dredging in the downstream area is done to slow down the rate of siltation in Kendari Bay.